Mapping China's approach to energy cooperation: The primacy of national interest - Van Min, Pham (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This paper engages with the current debate on China’s global search for energy security with a particular focus on China’s approach to international energy cooperation. It argues that China’s approach involves three stages:-first, China behaves as a passive follower to the cooperative agenda proposed by other interested parties;-it then becomes more active to propose issues for cooperation which best serves its domestic needs;-finally, if it succeeds, China will demonstrate positive commitments to promoting cooperation. Otherwise, it returns to the first stage by showing no keen interests in cooperation. China also adopts passive behaviour towards any energy-related issue that could challenge its sovereignty. This paper uses Sino-Japanese, Sino-US energy cooperation and China’s involvement in East Asian energy multilateralism, namely ASEAN+3 and East Asian Summit as case studies. The underlying factor throughout this approach is China’s national interest. This approach can provide implications for China’s behaviour in other areas such as trade and even territorial disputes. Understanding China’s behaviour is essential if countries wish to cooperate with China and to promote international energy cooperation.Received: 10th March 2016; Revised: 29th March 2016; Accepted: 17th April 2016